(untitled) (Princeton, 1965)
Dealing with the extraordinary economic modernization that has been taking place in Japan since 1868, this is a study of Japan's historical opportunities and the human responses that have molded the vigor of her development. The first half of the book concentrates on the Meiji Era, 1868-1911, when the foundations of modern industrial society and the modem state were being created. The second half focuses on Japan since World War II. The sixteen authors who have contributed to this volume represent much of the best informed scholarship on the economic factors of Japanese modernization...
Keywords: Japan,Nhật Bản; Economic,Kinh tế